(untitled) (Research, Society and Development, 2021)
The assumptions of the second law of thermodynamics support the biophysical understanding of the economic theory that biodegradation of the environment is due to the effects of the entropy generated by the economy. World events between 1950 and 1970 made more evident negative effects of the dominant economic pattern. Thus, it became imperative to think about the environment in more organic terms to understand the role of human society and the importance of its actions toward sustainable development. As it promises to reconcile social, economic, and environmental objectives, this article seeks to analyze the bioeconomy as a path for sustainability in the Brazilian Amazon. The chosen study area is the Legal Amazon for considering its national relevance in issues involving sustainability. To support the analysis of qualitative and quantitative data, a literature review was carried out for a better interpretation of current phenomena involving the bioeconomy in the region. For results and discussion, descriptive statistics and time series (2010-2019) analyses were used. The study concludes that the Amazonian bioeconomy has the potential to add value to the Brazilian national product, as well as to generate local employment and to contribute towards environmental conservation through activities with low impact. Nevertheless, there are challenges such as the need to advance in the knowledge base and in the required infrastructure to promote development in the region’s bioeconomy.